Poultry offal meal production conditions impact meal quality and digestibility in Atlantic salmon - M. M. Rocker; M. J. Lewis; T. S. Mock; D. S. Francis; F. Bellagamba; V. M. Moretti; G. P. Quinn; R. P. Smullen; G. M. Turchini (Aquaculture, 2021)
Aquafeed manufacturers are increasingly interested in ensuring consistently high-quality products, while relying heavily on poultry offal meal (POM), which is inevitably variable. This study examined the chemical composition of 22 different commercially and experimentally produced POM to determine which chemical variables best predict in vivo protein digestibility in Atlantic salmon (Salmo salar) and to evaluate which production variable, rendering temperature or raw material freshness, has a greater impact on digestibility. The chemical composition of commercially and experimentally produced POM was extremely variable. Significant relationships were found between in vivo dietary protein digestibility and D-glutamic acid (R2 = 0.64) and D-aspartic acid (R2 = 0.62). Rendering temperature and raw material freshness had significant effects on D-amino acids and biogenic amines. D-glutamic and D-aspartic acids may provide rapid-assessment indication of POM quality, as these D-amino acids were linked to protein digestibility and affected by the production variables. This study supports the well-held notion that POM is subject to significant variability and addresses the specific chemical characterisation of POM and the production conditions which impact nutrient digestibility in Atlantic salmon. These results prove beneficial to aquafeed manufactures aiming to ensure consistency and high nutritional quality in protein sources for aquafeed.